1996
DOI: 10.1093/ndt/11.6.1003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ramipril, nifedipine, and moxonidine on glomerular morphology and podocyte structure in experimental renal failure

Abstract: (i) Despite comparable reduction in systolic blood pressure, different classes of antihypertensive agents had diverse effects on renal damage in subtotally nephrectomized rat. This observation is consistent with specific, non-hemodynamic actions of anti-hypertensives. (ii) Glomerular and tubulointerstitial damage are prevented by treatment with ACE inhibitors and antisympathotonic agents, but not with the calcium antagonist nifedipine. In contrast, renal vascular changes were also prevented by nifedipine. (iii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 33 publications
(48 reference statements)
4
36
0
4
Order By: Relevance
“…Published data show that enalapril is effective in the therapy of glomerulosclerosis accompanying a variety of kidney diseases [4,12,15]. There are ambiguous data on the delayed effect of enalapril administered during the early ontogeny.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Published data show that enalapril is effective in the therapy of glomerulosclerosis accompanying a variety of kidney diseases [4,12,15]. There are ambiguous data on the delayed effect of enalapril administered during the early ontogeny.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on animals with experimental [3,4,8,15] and inherited arterial hypertension [10,14] yielded ambiguous results. It was concluded that the presence and degree of the delayed hypotensive effect depend not only on the type of drugs, but also on the terms and duration of therapy.…”
mentioning
confidence: 99%
“…Kidneys were then dissected in 1 mm thick slices perpendicular to the longitudinal axis. Tissue sampling for morphometric and stereological analysis was performed using the area weighted sampling technique as previously described [32]. The kidney slices were embedded in paraffin and 3 µm thick sections were prepared and stained with hematoxylin/eosin (HE), periodic acid Schiff (PAS), and Sirius red (fibrous tissue stain).…”
Section: Methodsmentioning
confidence: 99%
“…Glomerular geometry was analyzed as described in detail previously [32, 33]: Volume density (VV) of glomeruli and cortex were measured by point counting at a magnification of 200x on HE sections and corrected for tissue shrinkage. Then, the number of glomeruli per area (NA) was assessed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation